Desain Dan Analisis Struktur Rangka Motorcycle Lift Menggunakan Perangkat Lunak Solidworks - Kristomus Boimau; Matheus M. Dwinanto; Valerius G. Seranian (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2021)
Structural analysis is the science of determining the effects of loads on physical structures and their components. Structural analysis combines the fields of engineering mechanics, materials engineering, and engineering mathematics to calculate deformation of structures, internal forces, stresses, bearing reactions, accelerations, and stability. The designer chooses solidwork software for design and analysis because this software can properly simulate the design and calculation of forces on machine tools and elements. Solidwork contains a collection of simulation programs that are easy to use and can be used to create part programs and material selection used for mechanical analysis at work in order to obtain stress, displacement and safety factors (factory safety). The designed motorcycle lift features a chrome stainless steel frame with a control system, with main dimensions 1800 mm length, 700 mm width and 200 mm height at minimum position, 200 kg weight and 855 mm maximum height reach. Based on the identification using REBA in the mechanical posture after the design, it was found that the risk level decreased compared to before the design, from a high risk level to a low risk level. The results of the mechanical evaluation of the use of the designed motorcycle lift, there are several things that have become shortcomings of this design, among others, in terms of the speed of time in raising the position of the motorbike and the boot of the motorcycle lift which is still too heavy.